PENERAPAN METODE DISKUSI UNTUK PEMBENTUKAN KARAKTER DAN HASIL BELAJAR SISWA - Nurbaiti, Nurbaiti (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This research is motivated by the importance of paying attention to youth behavior for the nation's future assets. This teenage period is always a difficult time for teenagers and their parents because association is increasingly rampant which can destroy the future of adolescents. In order for youth to be free from deviant behavior in education as a place for young people to study knowledge, they must provide materials to avoid deviant behavior in adolescent association, as was done by MTsN 2 Rokan Hulu Semester 2. This type of research uses descriptive qualitative. The population used was students at MTsN 2 Rokan Hulu semester 2. The results obtained in this study were that the discussion method was 100% effective because all students scored above the minimum completeness criteria (KKM) 73.